La psychanalyse, est-elle homophobe? - Mari Paz Rodríguez Diéguez (Criminocorpus)
This investigation aims to respond to the critiques certain authors of queer theory have addressed to Lacanian theory, namely the accusation of homophobia. At the end of his teaching, Lacan recognized « There is no sexual relation »; and with this aphorism, he opened the door to a new paradigm oriented by the real: jouissance that aims at the impossible of the sexual relation. This substitutive jouissance, as Jacques-Alain Miller named it, doesn’t distinguish between neurosis and perversion. This new reading which goes beyond the structural clinic springs from the Borromean knot, in other words, that which holds the symbolic, real, and imaginary registers of desire and jouissance together. We purport to overcome the Oedipus complex by way of the very last Lacanian teaching. In order to do so, we revisited Freud’s extremely well-known case of the “young homosexual woman”, starting from new historical elements published in her biography entitled, Sidonie Csillag: Jeune Homosexuelle chez Freud, lesbienne dans le siècle. We will regard homosexuality from another angle thanks to the new Borromean conception. Our goal shall be to find the convergences between this new Borromean paradigm of psychoanalysis and Queer theory.